PENYULUHAN DAN PEMBUATAN PENYIMPANAN AIR HUJAN/ IONIZER AIR DI SMK 6 KOTA BANDUNG - Ekki Kurniawan; Erna Sri Sugesti; Uke Kurniawan; Akhmad Hambali; Irham Mulkan Rodiana (LPPM Universitas Bina Bangsa, 2024)
In 2045, Indonesia is projected to become a developed country, with the 4th largest economy in the world. This prediction is motivated by the demographic bonus that will occur in 2030-2040. This is an advantage if you succeed in educating the younger generation. On the other hand, it will be a